NATURE IN COLORS EXPRESSED BY THE ARTIST - Abdurashidova Zulfiya Alisher qizi (Journals Park Publishing, 2024)
The article Uzbekistan Descriptive Art Development for Contribution added artist Orol Tansikbayev's life and creativity the information given The artist's creative works and their analysis. Creative in his works, the landscape genre about creative his works commonly illuminated given
Keywords: Orol Tansikboyev, artist, landscape, creation, work, exhibition, color, landscape.